2016
DOI: 10.1038/srep39409
|View full text |Cite
|
Sign up to set email alerts
|

HBV/HCV dual infection impacts viral load, antibody response, and cytokine expression differently from HBV or HCV single infection

Abstract: Hepatitis B virus/hepatitis C virus (HBV/HCV) dual infection is common among high-risk individuals. To characterize the virological and immunological features of patients with HBV/HCV dual infection, we enrolled 1,049 individuals who have been identified as injection drug users. Patients were divided into single and dual infection groups according to the serological markers. We found the average HCV RNA level was significantly lower; however, HBV viral load was significantly higher in HBV/HCV dual-infected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In contrast, anti-E2 antibody frequency and levels were found to be lower in the context of HCV/HBV coinfection compared to HCV monoinfection in two other studies (116). …”
Section: Viral-viral Interaction In the Setting Of Hcv/hbv Coinfecmentioning
confidence: 67%
See 2 more Smart Citations
“…In contrast, anti-E2 antibody frequency and levels were found to be lower in the context of HCV/HBV coinfection compared to HCV monoinfection in two other studies (116). …”
Section: Viral-viral Interaction In the Setting Of Hcv/hbv Coinfecmentioning
confidence: 67%
“…Many studies report that HCV is the dominant virus with relative suppression of HBV replication (111115). In contrast, other studies have found that HBV is more dominant, or that there is no dominant virus with reciprocal inhibition compared to either virus monoinfection (116121), and one other study showed higher HCV RNA clearance rates in coinfection compared to HCV monoinfection (74% vs. 14%) (122). However many of these studies are largely cross-sectional with only one time point for HCV and HBV testing, and may explain the widely varying clinical presentations described.…”
Section: Viral-viral Interaction In the Setting Of Hcv/hbv Coinfecmentioning
confidence: 87%
See 1 more Smart Citation
“…Whether and how these viruses interfere reciprocally may dependent on the infection order and disease stage. Of note, we and other colleagues showed that HCV replication was suppressed during HBV/HCV coinfection compared with HCV monoinfection . In this cohort, we also found the fact that HBV replication dominates during HBV/HCV coinfection (data not shown), and it may partially explain altered distribution of cTfh subsets within HBV/HCV coinfection distinct from HCV monoinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, as in most countries with intermediate endemicity for HBV infection, most of these infections occurred through horizontal transmission during infancy or early childhood; thus, patients had HBV infection for many years before being infected by HCV. As proposed by Chen et al , patients who acquired HCV infection later than HBV infection have a minority of hepatocytes uninfected by HBV and thus “available” for HCV superinfection; this unequal distribution of the coinfection leads to HBV dominance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%